Growth Performance of Dalbergia sissoo, Eucalyptus grandis, Michelia champaca, Grevillea robusta, Bauhinia variegatra and Bauhinia purpurea for Planting under Social Forestry Programmes - Bahuguna, V. K.; Drawan, V. K. (Indian Forester, 1990)
This paper presents the results of an experiment laid out to assess the performance of Dalbergia sissoo, Eucalyplus grandis, Michelia champaca, Grevlliea robusta, Bouhinia variegata and B. purpurea under Dehra Dun conditions. The experiment was laid out in July 1985 and concluded in Sept. 1989. Based on the results of growth and biomass production, it is reported that the performance of Michelia champaca, Grevillea robusta, Eucalyptus grandis and Dalbergia sissoo have been encouraging under Dehra Dun conditions.